Behavior of Concrete Reinforced with Fibers from End-of-Life Tires Under High Compressive Strain Rates - PAJAK, Małgorzata; JANISZEWSKI, Jacek; KRUSZKA, Leopold (Engineering Transactions, 2019)
The behavior of concrete reinforced with the fibers obtained from the end-of-life tires under high compressive strain rates was the scope of this research. The laboratory investigations were performed using the Hopkinson Pressure Bar with a diameter of 40 mm. The waste fibers with untypical geometrical parameters were applied to concrete with a dosage of 30 kg/m3. The pronounced increase of compressive strength of the RSFRC, when subjected to high strain rates, was observed. The strain rate sensitivity of the RSFRC expressed by DIF was comparable to the other results presented in the literature.